1971
DOI: 10.2134/agronj1971.00021962006300020050x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Field Measurement of Leaf Water Potential in Soybean1

Abstract: Leaf water potentials of soybeans (Glycine max L. Merr.) were compared by two methods, the pressure chamber and the thermocouple psychrometer. A correlation coefficient of 0.957 was found for the two methods at leaf water potentials ranging from ‐3 to ‐25 bars. The pressure chamber method was used to measure the leaf water potential of several hundred soybean plants in different cultural studies in 1969 at Urbana, Illinois and found to be a rapid, efficient method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1972
1972
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…Leaf water potential was tneasured with a pressure chatnber (tnodel 3000, Soil Moistute Equiptnent Corpotation, Santa Bat bat a, CA, USA) on fully mature leaves from Ihe upper canopy. It had previously been determined that leaf water potentials measuted by pressute chamber and the isopiestic technique wete not significantly diffetent, a result also obtained by Boyer & Ghorashy (1971). Imtnediately after water potential measutetnents, the conductance of individual leaves from a similar location was tneasured with a steady-state porometer (L1I600, LICOR, Lincoln, NE, USA) on 5-7 leaves per ttay.…”
Section: Plant Water Use and Water Statusmentioning
confidence: 82%
“…Leaf water potential was tneasured with a pressure chatnber (tnodel 3000, Soil Moistute Equiptnent Corpotation, Santa Bat bat a, CA, USA) on fully mature leaves from Ihe upper canopy. It had previously been determined that leaf water potentials measuted by pressute chamber and the isopiestic technique wete not significantly diffetent, a result also obtained by Boyer & Ghorashy (1971). Imtnediately after water potential measutetnents, the conductance of individual leaves from a similar location was tneasured with a steady-state porometer (L1I600, LICOR, Lincoln, NE, USA) on 5-7 leaves per ttay.…”
Section: Plant Water Use and Water Statusmentioning
confidence: 82%
“…Our cut leaves had a wound surface area to leaf volume ratio of 1 to 2 cm2/cm3 of tissue. This amount of wounding is quite small and indeed if the leaf tissue were sunflower or pepper, we would not expect to find a deviation (2,6). The fact that water potentials measured Can.…”
Section: Tl7e Effects Of Cutting Leavesmentioning
confidence: 89%
“…Boyer (1967) and Boyer and Ghorashy (1971) demonstrated that the quantitative relationship between the xylem water potential and the balance pressure is valid only when the system is at equilibrium. The polyethylene bag and its moist lining were then removed from the leaf and the chamber was sealed.…”
Section: Xylem Pressrrre Potentirilmentioning
confidence: 99%
“…However, because they require a close temperature control and elaborate instrumentation, their use in plant water relation studies is restricted primarily to the laboratory. Comparisons of the pressure chamber measurements with thermocouple psychrometer measurements (Boyer and Ghorashy 1971;Blum et (11. Comparisons of the pressure chamber measurements with thermocouple psychrometer measurements (Boyer and Ghorashy 1971;Blum et (11.…”
Section: Introductionmentioning
confidence: 99%